2004
DOI: 10.1023/b:ddas.0000020489.96582.cd
|View full text |Cite
|
Sign up to set email alerts
|

Schatzki's Ring: To Cut or Break an Unresolved Problem

Abstract: Symptom assessment has been proven to be less reliable than barium pill testing for success of dilation of peptic strictures. Schatzki's ring also has a high recurrence rate. Our aim here was to compare the efficacy of single dilatation with a 54-F Savary dilator and electrosurgical ring incision for symptomatic Schatzki's rings. Schatzki's ring patients who failed to pass a 12.7-mm barium pill were randomized to dilatation with a 54-F Savary dilator or four quadrant incisions with a needle knife. All received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Moreover, patients do not have to enter dilatation programs following this procedure. This supports the eYcacy of a single dilatation for treatment of these lesions, which, however, tend to form again with time [14].…”
Section: Results Of Dilatationssupporting
confidence: 62%
“…Moreover, patients do not have to enter dilatation programs following this procedure. This supports the eYcacy of a single dilatation for treatment of these lesions, which, however, tend to form again with time [14].…”
Section: Results Of Dilatationssupporting
confidence: 62%
“…Perforation has never been reported. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] After esophageal dilation with bougies or balloons, perforation and/or hemorrhage is reported to occur in 0.1% to 0.4% of patients. 1,2,[7][8][9]39 This may be a true difference; however, SB is judged by many to be a more straightforward procedure than EI and may therefore be performed by less experienced endoscopists.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,[11][12][13][14][15][16] Electrocautery incision (EI) therapy of GI strictures has been reported in a small series of patients with a Schatzki ring and has also been used for the management of circular anastomotic strictures after GI surgery. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] In our series of 20 patients with gastroesophageal anastomotic strictures refractory to SB, EI with a needle-knife proved to be safe and effective. 21 Based on these results, we designed a prospective, randomized, controlled study.…”
mentioning
confidence: 99%
“…A similar technique has been described in strictures owing to some other causes. [22][23][24][25][26] This study has the disadvantage of being retrospective in nature. However, we observed that the strictures induced by AP were not confined to a particular segment of the esophagus and were seen in all parts of the esophagus.…”
Section: Discussionmentioning
confidence: 99%